Fibre optic pressure sensors in healthcare applications - Abeywardena, Chalani Lakshani (2021)
This PhD thesis provides an extensive description of the development of two fibre optic pressure sensors for applications in health care: (i) a miniature fibre optic Fabry–Perot pressure sensor for fluid pressure measurements in invasive blood pressure monitoring and; (ii) a highly sensitive fibre Bragg grating sensor for contact/interface pressure measurement. The fibre optic Fabry-Perot pressure sensor has a diameter of 125 μm and is created by forming a cavity at the tip of a single-mode optical fibre. Parylene films were used as the pressure-sensitive diaphragm. The performance of three sensors with different aspect ratios has been investigated. The pressure sensing range of ~10 kPa (diastolic pressure)- ~15 kPa (systolic pressure) was targeted; sensor with the cavity of 70 μm in diameter and cavity length of 87 μm is able to sense within a range of 0- 18 kPa with an average sensitivity of 0.12 nm/kPa and response time of 3 seconds. The temperature sensitivity of 0.084 nm/°C was observed. Hysteresis and wavelength drift were observed for the sensors, which may be due to the permeability of the Parylene film to the air. Solutions for reducing hysteresis, wavelength drift and temperature cross-sensitivity are discussed in detail. Fibre Bragg grating (FBG) sensor technology is an ideal candidate for contact pressure measurement in compression therapy, pressure ulcer or prosthetics due to its many advantages such as conforming to body parts, small size, biocompatibility and multiplexing capabilities. A successful mathematical model for an FBG contact pressure sensor for healthcare applications has been presented and experimentally validated. The model has been compared with previous studies reported in the literature and takes into account birefringence. The highest sensitivity was achieved for the disc shape with a sensitivity of 0.8719 nm/MPa for a diameter of 5.5 mm, thickness of 1 mm and Young’s modulus of 20 MPa. This sensor was comprised of a 3 mm long FBG 6 centrally located in the patch. This is a pressure sensitivity of ~270 times increase when compared with a bare FBG reported in the literature. Birefringence effect was observed for the disk patch for pressures larger than 2.6 MPa. Even though FBGs provide high sensitivity in contact pressure sensing in healthcare, the potential applications are limited by the size and cost of commercially available FBG interrogators. A successful first attempt towards the development of a single channel compact FBG interrogation was accomplished. The system consists of a three-section distributed Bragg Reflector (DBR) tuneable laser, microcontroller unit, precision 5 channel current driver IC, photodiode circuit and a temperature controller IC. The tuneable laser was calibrated within 1535-1544 nm wavelength range to produce three current–wavelength lookup tables for wavelength resolution of 1 nm, 0.1 nm, 0.01 nm which is dependent on the current resolution. Futureworkincludesaddingpowercircuitry, a photodiode circuit and a feedback circuit to minimize power fluctuations. The system was tested compared to the commercial Smartscope FBG interrogator.